The Activity of the Spirit in the Old Testament as Donation. An Approach to the Balthasarian Pneumatology of Theo-Logic III: The Spirit of the Truth (Teología, 2018)
This article describes the activity of the Holy Spirit in the Old Testament in accordance with the Pneumatology that H. U. von Balthasar proposes in Theo-logic III: The Spirit of the Truth. In view of the lack of an Old Testament’s systematic theology in this book, the author suggests to arrange the presence of the Spirit in two periods: one is his permanent activity since creation, especially in the history of Israel, anointing judges, prophets and kings, and in his inherent unity with another figure of mediation: the Word. The article also suggests an interpretation of the prophet Ezekiel’s view of the glory under the terms of phenomenology of donation, in order to present this event in the perspective of the activity as part of the preceding Pneumatology to the Incarnation as Balthasar proposes.
Keywords: H. U. von Balthasar and the “Spirit of the Truth”; Pneumatology of the Old Testament; The Spirit in the Old Covenant; ‘Spirit’ and ‘Word’; Phenomenology of Donation